WEB APPLICATION ARCHITECTURE DESIGN FOR TRAFFIC FLOW MANAGEMENT SIMULATION - FirsovО. D.; Ulianovska, Yu. V.; Mormul, M. F.; Pikulin, D. O. (Systems and Technologies, 2023)
The work is devoted to the issue of designing a web application for simulating traffic at an intersection. The general scheme of the section of the city’s transport network was analyzed and ways of its improvement were proposed. Alternative parameters of the functioning of this model have been developed, as well as sequential algorithms (descriptive and graphic) for solving the problem of traffic modeling have been compiled. Detailed flowcharts of each stage were built and the best option for solving the problem was chosen.